INTEGRATION OF LOCAL WISDOM VALUES DERIVED FROM ACCULTURATION OF THE CHINESE ETHNIC CULTURE IN CATUR VILLAGE WITH THE P5 MERDEKA CURRICULUM - Ni Luh Putri Wirautami; Djono Djono; Sariyatun Sariyatun (SOSIOEDUKASI, 2026)
This study examines how the local wisdom embedded in the Chinese–Balinese cultural acculturation of Lampu Hamlet, Catur Village, can be integrated into the Projek Penguatan Profil Pelajar Pancasila (P5) within the Merdeka Curriculum. Unlike previous studies that primarily discuss local wisdom as cultural content, this research highlights living cultural acculturation as a contextual pedagogical resource for character education and identity development. A qualitative case study was conducted at SMA Negeri 1 Kintamani using participatory observation, in-depth interviews, and document analysis involving teachers, students, and school staff. The findings reveal that the values of tolerance, mutual cooperation, religiosity, social harmony, and cultural awareness embedded in Chinese Balinese acculturation provide authentic learning experiences that support the implementation of P5. More importantly, the study identifies a four-stage process of value internalization understanding, experiencing, reflecting, and character formation that enables students to reconstruct their local cultural identity while strengthening the dimensions of the Pancasila Student Profile. These findings demonstrate that living cultural acculturation can function not only as local cultural heritage but also as an innovative contextual learning resource for implementing the Merdeka Curriculum and fostering multicultural character education